Governance in a globalized world: the limitations of corporate social responsibility / Krista Bywater - Bywater, Krista (2010)
The Coca-Cola Corporation1 promotes itself as a responsible corporation while people from India and Colombia to the United States and Europe criticize the company's business practices. Coke, like many other transnational corporations (TNCs), has adopted corporate social responsibility (CSR) policies to protect its revenue and the reputation of its global goods and brand. The company continues to promote its CSR agenda to address the social opposition it has faced since re-entering India in 1993. Using the movement against Coke in India as a case study, this paper examines the problems with CSR and how firms can employ CSR policies to quell oppositional social movements. 2 Through initiatives such as corporate partnerships with development agencies and corporate sponsorship of non-governmental organizations (NGOs), companies, like Coca-Cola, blur the boundaries between markets and movements in order to minimize the effects of popular opposition to global goods. CSR is a discourse that helps companies "greenwash"3 (Greer and Bruno 1996) their images and appear more responsible without making meaningful changes to their business practices. Rather than being used to curtail the harmful effects of economic globalization and TNCs, CSR is typically employed to limit governmental regulation and justify increased foreign investment in the Global South (Blowfield 2005). As a result, CSR furthers the neoliberal agenda, which promotes economic globalization and foreign investment as the best means to achieve social and sustainable development.